Hedgehogs : everything about purchase, care, and nutrition - Vanderlip, Sharon Lynn (Complete pet owner's manual., 2010)
Hedgehogs raised domestically make interesting pets, but require close attention to their health needs. Get the information and advice you need to take good care of your hedgehog.